2019
DOI: 10.1111/jgs.15763
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of a Statin Trial in Older People

Abstract: See the Reply by https://doi.org/10.1111/jgs.15762.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Accordingly, the experts urge to include better representation of very old adults, women, underrepresented minorities, and individuals with various health status, cognitive, socioeconomic, and educational backgrounds in future trials. However, it may be challenging to recruit oldest patients for a placebo-controlled trial and it is feared that a potentially negative result (like lack of effect of statins in end-stage disease) would be wrongly applied to those older patients, whose treatment has been started earlier in life, simply because of age [ 45 ].…”
Section: Statin Treatment In Older Peoplementioning
confidence: 99%
“…Accordingly, the experts urge to include better representation of very old adults, women, underrepresented minorities, and individuals with various health status, cognitive, socioeconomic, and educational backgrounds in future trials. However, it may be challenging to recruit oldest patients for a placebo-controlled trial and it is feared that a potentially negative result (like lack of effect of statins in end-stage disease) would be wrongly applied to those older patients, whose treatment has been started earlier in life, simply because of age [ 45 ].…”
Section: Statin Treatment In Older Peoplementioning
confidence: 99%
“…To the Editor: Dr. Strandberg appropriately highlights challenges in the recruitment and conduct of a placebo‐controlled trial of statins for primary prevention of cardiovascular events among people 75 years and older . Consistent with his concerns about the frequent use of statins for primary prevention among adults older than 75 years, we found that 41% of participants 75 years or older without cardiovascular disease were already using statins in an integrated health delivery system in the United States .…”
mentioning
confidence: 51%
“…Typically, the prevalence of disability will grow due to aging; the World Health Organization estimated that 46.1% of the world populations older than 60 years are affected by moderate or severe disability. 1 It is known that China has the largest elderly population than any other countries; according to the China 2010 census, 6 the number of people aged 60 years and older was 177 million, accounting for 13.3% of the whole population. Old people with disabilities required more healthcare and clinical needs than those without disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor: Over a billion people, comprising 15% of the world's population, have some form of disability. 1 The number of disabilities is continuing to grow due to population aging and increased accidents and chronic disorders. 2 China has the largest population of elderly people 3 ; however, studies on disabilities in Chinese elderly people have rarely been reported.…”
Section: Elderly People With Disabilities In Chinamentioning
confidence: 99%